Initial steps in selenocysteine biosynthesis: The interaction between selenocysteine lyase and selenophosphate synthetase - Scortecci, Jessica F.; Serrao, Vitor Hugo B.; Fernandes, Adriano F.; Basso, Luis G. M.; Gutierrez, Raissa F.; Araujo, Ana Paula U.; Neto, Mario O. [UNESP]; Thiemann, Otavio H. (Elsevier B.V., 2020)
The selenocysteine (Sec) incorporation is a co-translational event taking place at an in-frame UGA-codon and dependent on an organized molecular machinery. Selenium delivery requires mainly two enzymes, the selenocysteine lyase (CsdB) is essential for Sec recycling and conversion to selenide, further used by the selenophosphate synthetase (SelD), responsible for the conversion of selenide in selenophosphate. Therefore, understanding the catalytic mechanism involved in selenium compounds delivery, such as the interaction between SelD and CsdB (EcCsdB.EcSelD), is fundamental for the further comprehension of the selenocysteine synthesis pathway and its control. In Escherichia coli, EcCsdB.EcSelD interaction must occur to prevent cell death from the release of the toxic intermediate selenide. Here, we demonstrate and characterize the in vitro EcSelD.EcCsdB interaction by biophysical methods.The EcSelD.EcCsdB interaction occurs with a stoichiometiy of 1:1 in presence of selenocysteine and at a low-nanomolar affinity (similar to 1.8 nM). The data is in agreement with the small angle X-ray scattering model fitted using available structures. Moreover, yeast-2-hybrid assays supported the macromolecular interaction in the cellular environment. This is the first report that demonstrates the interaction between EcCsdB and EcSelD supporting the hypothesis that EcSelD.EcCsdB interaction is necessary to sequester the selenide during the selenocysteine incorporation pathway in Bacteria. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Selenophosphate synthetase; Selenocysteine lyase; Selenocysteine biosynthesis